2015
DOI: 10.1016/j.sbspro.2015.06.369
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Research on General Internet Usage Patterns of Undergraduate Students

Abstract: As a growing trend in the world, internet-based research has become vital in one's daily life. The internet use by students has increased dramatically in recent years and also surfing the internet has become an important part of general student life. Furthermore, information technologies (IT) have greatly expanded into the field of education in last two decades. The aim of this research is to summarize the internet usage patterns of undergraduate students and to show in what density students utilize from inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 3 publications
0
19
2
Order By: Relevance
“…According to a study on North American Colleges and Universities, over 80% of Faculty administration believe that web based technology is a key contributor to student success. The study also noted that 62% of faculties in the USA and Canada use the Internet to prepare coursework, 56% use the web to supplement textbooks, while 51% use it to ensure up-to-date course content (Deniz & Geyik, 2015). A study by Ruzgar (2005) on the purpose of Internet use and learning via Internet among Turkish college students concluded that the Internet has become an integral part of college life, and its usage is almost 100% among students.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…According to a study on North American Colleges and Universities, over 80% of Faculty administration believe that web based technology is a key contributor to student success. The study also noted that 62% of faculties in the USA and Canada use the Internet to prepare coursework, 56% use the web to supplement textbooks, while 51% use it to ensure up-to-date course content (Deniz & Geyik, 2015). A study by Ruzgar (2005) on the purpose of Internet use and learning via Internet among Turkish college students concluded that the Internet has become an integral part of college life, and its usage is almost 100% among students.…”
mentioning
confidence: 98%
“…Askoy (2012) opines that the reason for the rapid growth is the global availability of the Internet which significantly makes it different from other information media. It is reported that ease of work and time-saving are the reasons of Internet use among students (Bashir, Mahmood, & Shafique, 2008;Deniz & Geyik, 2015). According to a study on North American Colleges and Universities, over 80% of Faculty administration believe that web based technology is a key contributor to student success.…”
mentioning
confidence: 99%
“…12 The Internet has become a functional tool for a university student to acquire information and interact with others. 13 Male university students mainly have been using the internet to socialize to their peers more than girls. 14 Various risk factors have been identified predisposing to the pathological internet use including being a male, young age group, time spent online, using social and gaming applications and psychosocial factors such as neuroticism, depression or anxiety.…”
mentioning
confidence: 99%
“…A study of Economics students' uses of the Internet at Istanbul University revealed that the most of the participants (about 76 %) make use of electronic resources for purposes including social networking, download of movies and music, entertainment as well as pastime such as shopping and playing games. The use of electronic resources for homework and getting knowledge for academic purposes via the Internet (24 %) of the participants ranked below shopping online, playing games and Internet surfing 23 . The researchers concluded that information technologies and the Internet was an important part of university students' daily life, but most of the students do not utilse the Internet for academic-related readings and research needs 23 .…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The use of electronic resources for homework and getting knowledge for academic purposes via the Internet (24 %) of the participants ranked below shopping online, playing games and Internet surfing 23 . The researchers concluded that information technologies and the Internet was an important part of university students' daily life, but most of the students do not utilse the Internet for academic-related readings and research needs 23 .…”
Section: Findings and Discussionmentioning
confidence: 99%